2019
DOI: 10.1108/tr-10-2018-0153
|View full text |Cite
|
Sign up to set email alerts
|

The role of job rotation in enhancing employee performance in the Egyptian travel agents: the mediating role of organizational behavior

Abstract: Purpose The purpose of this paper is to propose and test a conceptual model that explores the effect of job rotation on employees' performance through the mediating role of organizational behavior (namely, motivation, organizational commitment, job satisfaction, job involvement and job burnout). Design/methodology/approach Data are gathered from employees in the tourism and aviation departments at travel agents category A in Egypt. In total, 788 questionnaires are analyzed using regression-based partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
1
16
3
1
Order By: Relevance
“…In the field of tourism, job performance has been associated with job rotation and organizational behavior (Al-Romeedy, 2019), transformational leadership, identification and engagement (Buil et al , 2019), quality of work-life, job satisfaction and work motivation (Sari et al , 2019) and psychological contract and organizational commitment (Tsui et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of tourism, job performance has been associated with job rotation and organizational behavior (Al-Romeedy, 2019), transformational leadership, identification and engagement (Buil et al , 2019), quality of work-life, job satisfaction and work motivation (Sari et al , 2019) and psychological contract and organizational commitment (Tsui et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among other negative variables, job burnout is the most frequently researched (Al-Romeedy, 2019;Johnson and Spector, 2007;Montgomery et al, 2006). Job burnout is a key element that causes adverse salary balance, recognition, support and advancement, which are not expected in the tourism industry (Pienaar and Willemse, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Properly conducted job rotation programs will enrich employees with both new skills and knowledge in different job functions (Oparanma & Nwaeke, 2015). Hence, in line with the findings of Kampokotter, Harbing, and Sliwka (2018), Oparanma and Nwaeka (2015), Romeedy (2019) and many researchers have concluded that job rotation has positive impact on employee performance, the above hypothesis is constructed.…”
Section: Job Rotationmentioning
confidence: 65%